Pengaruh Kepuasan Kerja dan Gaya Kepemimpinan Transformasional terhadap Keinginan Keluar Karyawan dengan Komitmen Organisasi sebagai Variabel Mediasi (Studi Kasus Di CV. Putra Tama Jaya) (Universitas Negeri Semarang, 2014)
The purpose of this study is to know there any direct and indirect relationship between job satisfaction, organizational commitment and transformational leadership styles and relationship to turnover intention. The population is 294 people Blockboard production employees of CV Putra Tama Jaya and 170 samples obtained using the Slovin formula. Methods of data collection using questionnaires, methods of descriptive analysis, multiple regression analysis and partial and path analysis using SPSS for Windows version 16. The results, there is a direct effect of job satisfaction on employee turnover intention (0.025<0.05), job satisfaction on organizational commitment (0.007<0.05). of organizational commitment on the turnover intention (0.023<0.05), transformational leadership style to organizational commitment (0.000<0.05), so that H1, H2, H3, and H4 is accepted, there is no direct relationship of transformational leadership style against the turnover intention (0.984> 0.05) H5 is not acceptable. Organizational commitment does not mediate the relationship between job satisfaction and the turnover intention against the wishes of transformational leadership style H6 and H7 out so not accepted.